Pengaruh Penanaman Modal Dalam Negeri dan Penanaman Modal Asing Terhadap PDRB Sektor Pertanian di Provinsi Bali - ALFENCIUS MULATUA MALAU; MADE SUDARMA; I NYOMAN GEDE USTRIYANA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2015)
Abstract Effect of Foreign Investment Investment (FDI) and Domestic Investment (DCI) to GDP Agriculture in the province of Bali Economic development is a series of effort to improve living standards and create a more equitable income among the various communities, the Province of Bali as one of the good economic development to be studied. Issues examined in this study was aimed to determine the factors that influence the Gross Regional Domestic Product (GDP) in the province of Bali and the influence of foreign direct investment (FDI) and domestic investment (DI) to GDP of agriculture sector in the province of Bali. The analysis method used in this research is double regression or econometric test multiple linear regression using SPSS 22. By converting the original data into a LOG the results showed that foreign direct investment (FDI) and domestic investment (DCI affect the sector GDP agriculture in the province of Bali, with a coefficient of determination (R2) of 71.3 percent, so the percentage contribution of the influence of the independent variables (domestic and foreign) to the dependent variable (GDP) amounted to 71.3 percent. Variations of the independent variables used in the model (DCI and PMA) were able to explain 71.3 percent of the variation of the dependent variable (GDP).